52.0k views
2 votes
Find the zeros of the function.

Enter the solutions from least to greatest.
h(x) = (-4x – 3)(x – 3)
lesser x =
greater x =

2 Answers

5 votes

Answer:

x = -3/4 or x = 3

Explanation:

Solve for x over the real numbers:

(-4 x - 3) (x - 3) = 0

Hint: | Find the roots of each term in the product separately.

Split into two equations:

-4 x - 3 = 0 or x - 3 = 0

Hint: | Look at the first equation: Divide both sides by the sign of the leading coefficient of -4 x - 3.

Multiply both sides by -1:

4 x + 3 = 0 or x - 3 = 0

Hint: | Isolate terms with x to the left hand side.

Subtract 3 from both sides:

4 x = -3 or x - 3 = 0

Hint: | Solve for x.

Divide both sides by 4:

x = -3/4 or x - 3 = 0

Hint: | Look at the second equation: Solve for x.

Add 3 to both sides:

Answer: x = -3/4 or x = 3

User Huan
by
4.9k points
3 votes

Answer:

lesser x = -3/4

greater x =3

Explanation:

h(x) = (-4x – 3)(x – 3)

Set the function equal to zero to find the zeros

0 = (-4x – 3)(x – 3)

Using the zero product property

0 = (-4x – 3) 0=(x – 3)

Solve each equation

3 = -4x 3 =x

-3/4=x 3 =x

lesser x = -3/4

greater x =3

User Altso
by
4.5k points